Lymphocytes Mitochondrial Physiology as Biomarker of Energy Metabolism during Fasted and Fed Conditions - Erika Cortez; Fabiana A. Neves; Amélia F. Bernardo; Ana Carolina Stumbo; Laís Carvalho; Érica Garcia-Souza; Rosely Sichieri; Anibal S. Moura (The Scientific World Journal)
Mitochondria are central coordinators of energy metabolism, and changes of their physiology have long been associated with metabolic disorders. Thus, observations of energy dynamics in different cell types are of utmost importance. Therefore, tools with quick and easy handling are needed for consistent evaluations of such interventions. In this paper, our main hypothesis is that during different nutritional situations lymphocytes mitochondrial physiology could be associated with the metabolism of other cell types, such as cardiomyocytes, and consequently be used as metabolic biomarker. Blood lymphocytes and heart muscle fibers were obtained from both fed and 24 h-fasted mice, and mitochondrial analysis was assessed by high-resolution respirometry and western blotting. Carbohydrate-linked oxidation and fatty acid oxidation were significantly higher after fasting. Carnitine palmitoil transferase 1 and uncouple protein 2 contents were increased in the fasted group, while the glucose transporters 1 and 4 and the ratio phosphorylated AMP-activated protein kinase/AMPK did not change between groups. In summary, under a nutritional status modification, mitochondria demonstrated earlier adaptive capacity than other metabolic sensors such as glucose transporters and AMPK, suggesting the accuracy of mitochondria physiology of lymphocytes as biomarker for metabolic changes.